Conversion of Tannery Solid Wastes into Fuel Briquettes Using Wastepaper as a Binder - Desbelom Welegebrial Hagos; Mebrahtom Gebresemati Weldehans; Gebreyohannes Gebrehiwot Tesfay; Teklemariam Negash Reda (Textile & Leather Review, 2023)
The disposal of tannery solid waste (TSW) and the need for clean and affordable energy are two pressing issues. Converting TSW into briquettes could be a solution to both problems. This paper focuses on preparing and characterizing fuel briquettes from TSW using a wastepaper as a binder. Raw TSW samples were obtained from the nearby leather industry, sun-dried, treated, carbonized, and reduced to a size of less than 2 mm. The carbonized TSW was mixed with a wastepaper binder (WPB) in different combinations (100:0, 80:20, 60:40, 40:60, 20:80) and converted into briquettes using a hand-press briquette machine. Five briquettes were produced, and sun-dried for one week. The proximate analyses and calorific values of the resulting briquettes were determined in accordance with ASTM analytical methods. The briquettes had a moisture content of 1.30±0.01–5.30±0.10%, volatile matter of 4.01±0.09–10.21±0.18%, ash of 2.80±0.04–5.50±0.13%, fixed carbon of 79.00±0.54–91.90±0.36%, and calorific value of 20.48±0.08–21.09±0.04 MJ/kg. Results showed that a briquette comprised of 80% TSW and 20% WPB has a higher calorific value of 21.09±0.04 MJ/kg. This study demonstrates the feasibility of producing affordable and clean briquettes from an admixture of TSW and WPB. It also shows that briquette production can help reduce solid waste disposal in the tannery industry.